2016
DOI: 10.14814/phy2.12862
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction combined with a maternal high-fat diet increases hepatic cholesterol and low-density lipoprotein receptor activity in rats

Abstract: Intrauterine growth restriction (IUGR) and maternal consumption of a high‐saturated‐fat diet (HFD) increase the risk of hypercholesterolemia, a leading cause of morbidity and mortality. Many pregnant women eat a HFD, thus exposing the fetus to a HFD in utero. The cumulative effect of in utero exposure to IUGR and a HFD on offspring cholesterol levels remains unknown. Furthermore, little is known about the mechanism through which IUGR and maternal HFD consumption increase cholesterol. We hypothesize that IUGR c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Unless otherwise specified, at PND 21, offspring were separated from the dam, fasted overnight, and anesthetized with 8 mg/kg xylazine and 40 mg/kg ketamine before decapitation. We previously reported that dams fed the HFD had increased pregnancy weight gain by term gestation despite the same number of offspring per litter and same prepregnancy weight (72). Dams fed a HFD consumed the same calories as dams fed the regular diet, with no difference between dams who underwent uterine artery ligation and dams who had anesthesia as a control.…”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…Unless otherwise specified, at PND 21, offspring were separated from the dam, fasted overnight, and anesthetized with 8 mg/kg xylazine and 40 mg/kg ketamine before decapitation. We previously reported that dams fed the HFD had increased pregnancy weight gain by term gestation despite the same number of offspring per litter and same prepregnancy weight (72). Dams fed a HFD consumed the same calories as dams fed the regular diet, with no difference between dams who underwent uterine artery ligation and dams who had anesthesia as a control.…”
Section: Methodsmentioning
confidence: 88%
“…The University of Utah Animal Care Committee approved all animal procedures. The rat model of IUGR and a HFD was as previously described (72). In brief, 50-day-old male and nonpregnant female Sprague-Dawley CD rats were obtained from Charles River Laboratories (Wilmington, MA) and exposed to 12-h light-dark cycles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may be justified by the lower consumption of DLP diet in most of the periods, possibly due to the satietyogenic effect caused by the higher fat content of this diet, indicating that a dyslipidaemic diet does not necessarily induce obesity (15,18) . Pups from DLP dams of both sexes had LBW, probably because of the imbalance in the fatty acid ratio (35) and the reduction in energy content from protein, which is typical of a dyslipidaemic diet, and consequently, the low consumption of this nutrient from the indicated diet (36) . Regarding weight gain, from weaning to adulthood, there was a higher percentage of weight gain in pups from DLP dams compared with that in pups from CTL dams, which could be one of the negative impacts of dyslipidaemic diet consumption by dams (37)(38)(39) .…”
Section: Discussionmentioning
confidence: 99%
“…This observation could be a consequence of the replacement of a DLP diet with a normal diet or of body homoeostatic regulation, as demonstrated in previous studies in which offspring from dyslipidaemic dams presented normal levels of TC, HDL, LDL and TAG from 90 d of age (18,26) . Another study showed that pups from dams that received a diet rich in saturated fat and nursed up to 14 d had LBW and elevated LDL-cholesterol levels due to the increase in levels of LDL receptor protein, a receptor responsible for the metabolism of LDL-cholesterol; its high levels are linked directly to cases of familial hypercholesterolaemia (36) . The altered lipid profile and dysbiosis most prominently observed at 30 d but not 90 d of age reinforces the potential influence of an altered microbiome on host lipid metabolism (59) .…”
Section: Discussionmentioning
confidence: 99%